2009
DOI: 10.1007/s00248-009-9509-9
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics of a Single-Stage Sulfidogenic Bioreactor Treating Synthetic Zinc-Containing Waste Streams

Abstract: Waste streams from industrial processes such as metal smelting or mining contain high concentrations of sulfate and metals with low pH. Dissimilatory sulfate reduction carried out by sulfate-reducing bacteria (SRB) at low pH can combine sulfate reduction with metal-sulfide precipitation and thus open possibilities for selective metal recovery. This study investigates the microbial diversity and population changes of a single-stage sulfidogenic gas-lift bioreactor treating synthetic zinc-rich waste water at pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
0
10
1
Order By: Relevance
“…In Ollinkuilu, the SRB contributed with 0.2% of the total microbial community at −70 and −100 m depth. These values are significantly lower than in recent studies, which have typically shown the clear dominance of sulphate reducers in the reactors treating sulphate and metal rich waters [35], also in in situ reactors [36] and at low temperatures (9 °C) [37]. However, it is plausible that the most effective sulphate reduction is taking place at the bottom of the pit at 800 m depth to where the organic substrates and sulphate reducers have sedimentated.…”
Section: Resultscontrasting
confidence: 47%
“…In Ollinkuilu, the SRB contributed with 0.2% of the total microbial community at −70 and −100 m depth. These values are significantly lower than in recent studies, which have typically shown the clear dominance of sulphate reducers in the reactors treating sulphate and metal rich waters [35], also in in situ reactors [36] and at low temperatures (9 °C) [37]. However, it is plausible that the most effective sulphate reduction is taking place at the bottom of the pit at 800 m depth to where the organic substrates and sulphate reducers have sedimentated.…”
Section: Resultscontrasting
confidence: 47%
“…Recent studies have shown that anoxic reactors for the treatment of sulfate and metal‐rich waters are typically dominated by microbial sulfate reduction and that the phylogenetic diversity of the microbial communities is comparably small (Auvinen et al ., 2009; Bijmans et al ., 2009; Dar et al ., 2009). In contrast, the microbial community in our reactor was rather diverse, with the majority of the identified phylotypes belonging to SRB, homoacetogens and methanogens.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this scenario, the acetate degradation rate is affected by sulfate reduction, provoking its inhibition at low COD/SO 4 2-ratio (Omil et al 1998;Barber and Stuckey, 2000). At high COD/SO 4 2-ratio, acetogenesis is not inhibited by sulfate reduction, while the overall reactor performance is improved by molecular hydrogen removal (JWH et al, 1994;Kalyuzhnyi et al, 1998;Dar et al, 2009;Zhao et al, 2010). If SO 4 2-is present, SRB consumes molecular hydrogen at higher rates compared with methanogenic archeas because of its superior scavenging capability (Kristjansson et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Sulfate-reducing bacteria (SRB) can remove molecular hydrogen, allowing optimal performance of methanogenic microorganisms (JWH et al, 1994;Kalyuzhnyi et al, 1998;Dar et al, 2009;Zhao et al, 2010). Under anaerobic conditions, SRB, alone or in consortia, use sulfate as the main electron acceptor, consuming hydrogen and VFAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation